PENGEMBANGAN MEDIA DIGITAL ANIMATION BERBASIS CANVA PADA MATA PELAJARAN IPA MATERI TATA SURYA KELAS VI DI SDN MANGUNHARJO 1 KOTA PROBOLINGGO - Ibtihal, Karima Aliyahtus; Sriwijiyanti, Ribut Prastiwi; Jannah, Faridahtul (Universitas Mataram, 2024)
This activity was motivated by the unsatisfactory learning outcomes of students in science subjects, because students were not able to maximize the learning process. Lack of references in learning, lack of tools or media in learning, and the fact that students tend to understand learning using audio-visual better are the main factors. It is hoped that the Canva-based digital animation learning media can help teachers and students understand the solar system material. The research method used is the Borg & Gall development model with modifications to several aspects according to Utomo, Muslimin, and Darsikin, which include the preliminary study stage, product development stage, product validation stage, field trial stage and final product revision. Based on the research results, the development of Canva-based Digital Animation Learning Media in the Science Subject Solar System Material for Class VI was declared valid and practical with media expert validation results having a score of 46 with a percentage of 92%. The results of material expert validation obtained an overall score of 43 with a percentage of 86%. The results of learning practitioners obtained a total score of 48 with a percentage of 96%. And the assessment of science learning media with Canva-based digital animation resulted in an overall score of 1206 with a percentage of 86.14%. Based on this, the learning media developed is valid and practical for use in learning.